Autonomous Vehicles in Intralogistics - Hercog, Darko; Bencak, Primož (Digital Transformation in Logistics and Supply Chain Management, 2026)
Automated guided and autonomous vehicles are increasingly used in intralogistics processes to transport goods or support order picking. The publication provides a brief overview of the areas of automated and autonomous vehicles, their differences, and potential applications in intralogistics. The reader is introduced to the basic theory of the operation of autonomous mobile robots' (sub)systems (drive, sensors, localization, and navigation). For ease of understanding, web links to videos are added, which support the theory with a practical demonstration. Finally, in an example of the autonomous mobile robot MiR100, the operation of the mobile robot and its functions are presented.